Web-Based E-Learning System Optimization for SMA Negeri Ploso - Ady Luthfi Santosa; Munawarah Munawarah (NEWTON: Networking and Information Technology, 2025)
This research focuses on enhancing education at SMA Negeri Ploso by creating a web-based e-learning platform that offers organized access to educational resources, tasks, tests, and interaction between educators and students. The platform was developed to overcome the drawbacks of traditional teaching methods by providing more flexibility, easier access, and improved efficiency for both in-person and remote learning experiences. A qualitative methodology was used in conjunction with a development process that involved analyzing requirements, designing the system, implementing it, and conducting testing. The platform utilizes a structured access model based on user roles for administrators, educators, and students, allowing each group to execute specific functions aligned with their duties. Administrators handle user information, course management, and feedback, educators can upload and oversee educational content and assess students' work, while students can view course materials, turn in assignments, and check their grades. During the testing phase, it was confirmed that all primary functions worked properly and delivered accurate outcomes as designed. The user interface was crafted to be straightforward, easy to navigate, and usable on multiple devices including laptops, desktops, and smartphones. The launch of this web-based e-learning system significantly enhanced the adaptability and effectiveness of the educational process and has the potential for future developments such as incorporating online quizzes, automated feedback, and communication tools to further improve the learning journey.